2008
DOI: 10.1183/09031936.00125407
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of haem oxygenase-1 by alveolar macrophages in idiopathic pulmonary fibrosis

Abstract: Haem oxygenase (HO)-1 is an oxidative stress responsive protein that may be involved in the pathogenesis of interstitial lung disease.HO-1 expression in alveolar macrophages from bronchoalveolar lavage was investigated in 24 patients with idiopathic pulmonary fibrosis (IPF), 16 with sarcoidosis, 14 with hypersensitivity pneumonitis (HP) and 13 controls. Using immunocytochemistry, HO-1 expression in macrophages was scored semiquantitatively from 0-3 according to increasing intensity. The mean score of 100 macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 39 publications
3
24
1
Order By: Relevance
“…A pathogenic role for macrophages in pulmonary fibrosis has been postulated for many years, and described mechanisms have included overexpression of reactive oxygen species [147-151], proteinase-activated receptors [152-154], Fas ligand [155], and profibrotic cytokines [97,154,156-162]. …”
Section: Reviewmentioning
confidence: 99%
“…A pathogenic role for macrophages in pulmonary fibrosis has been postulated for many years, and described mechanisms have included overexpression of reactive oxygen species [147-151], proteinase-activated receptors [152-154], Fas ligand [155], and profibrotic cytokines [97,154,156-162]. …”
Section: Reviewmentioning
confidence: 99%
“…In patients with IPF there is an increase in oxidative damage and an increase in exhaled nitric oxide levels (Saleh et al, 1997;Paredi et al, 1999;Pullamsetti et al, 2011). Fibroblasts from IPF patients exhibit decreased nuclear Nrf-2 expression, and IPF patients have shown diminished antioxidative capacity by having decreased expression of Nrf-2 target genes and decreased levels of glutathione (Beeh et al, 2002;Peltoniemi et al, 2004;Vuorinen et al, 2008;Ye et al, 2008;Artaud-Macari et al, 2013). In addition, preclinical models show that mice with a genetic deletion of Nrf-2 have decreased survival and increased inflammation following BLM-induced damage (Kikuchi et al, 2010).…”
Section: Spl-334 Attenuates Inflammation and Fibrosis In The Lungsmentioning
confidence: 99%
“…In our model, these two processes appeared at different time points: at 7 days, the main manifestation was alveolitis, and then at 28 days, significant fibrosis appeared (Zheng et al, 2000;Lu et al, 2001;Ye et al, 2008). The current study identified that the model group had significant lung inflammation and fibrosis at 7 days.…”
Section: Discussionmentioning
confidence: 47%